PERCEPTUAL STANCE OF TEACHERS TOWARDS GENDER RESPONSE PEDAGOGICAL PRACTICES IN LIFE SKILL EDUCATION OF STUDENTS OF UNITED KINGDOM AND PAKISTAN - Rafia Naz; Dr. Manzoor Husain shah; Dr. Faheem Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
The current study focuses on the perceptual stance of teachers towards Gender Response Pedagogical (GRP) practices in life skill education of students of United Kingdom and Pakistan. The study was descriptive in nature. Teachers working in Abbottabad District, Pakistan, and Durham County, United Kingdom were included as target population. A sample of 320 teachers was selected out of 1618 teachers (1165 teachers from UK and 453 from Pakistan) through stratified sampling technique. A questionnaire was used including items related to Gender Response Pedagogy (GRP) in life skills education. The statistical result indicates that there is significant difference in the teachers working in UK and Pakistan regarding written and spoken language towards GRP implementation (p=.041<.05), giving equal attention to students in general as well as students of special needs (p=.036<.05) and teachers addressing the gender wise challenges (p=.031<.05).